(untitled) (Experimental biology, 2021)
Currently, efforts in sugar beet selection are aimed mainly at the creation of highly productive hybrid combinations which could be repeatedly derived from source line material. Naturally, the important step in this process is the development of constant homozygous source lines with high combining ability. Traditional approach in development of uniform sugar beet lines is based on repeated selection of self-pollinated lines. However, biennial lifecycle, cross-incompatibility and inbreeding depression all make breeding and maintaining the genetic homogeneity of sugar beet a challenging endeavor. To increase efficiency of development and preservation of genetic homogeneity of sugar beet lines used in hybrid production at the LLP “KazSRIA&PG”, our biotechnology lab started working on introduction of DNA markers into the selection process. Twenty sugar beet lines of various origins and levels of ploidy from LLP “KazSRIA&PG” collection have been studied, to assess their genetic homogeneity, using three SSR markers: Bvv21, Bvv53 and Bvv.